A morphometric study of acromion process of scapula and its clinical significance - Chandni Gupta; Abhilasha Priya; Sneha Guruprasad Kalthur; Antony Sylvan D'Souza (Wolters Kluwer Medknow Publications, 2014)
Objective: The acromion process is associated with a variety of ailments in the shoulder. Therefore, the aim of this study was to record and study all the morphometric values of the acromion process and its morphological features. Materials and Methods: The study was carried out on 50 unpaired dried scapulae. The length, width, and thickness of the acromion process were measured, and the length and width of scapula was also measured using vernier calipers. The acromiocoracoid and acromioglenoid distances were also measured. The shape, type of acromion process, and the presence of enthesophytes were noted and whether the anterior 2/3 rd of inferior surface of acromion process is rough or smooth was also noted. Results: The mean length, width, and thickness of acromion process were 4.21, 2.42, and 0.73 cm, respectively. The mean length and width of scapula were 13.93 and 10.14 cm, respectively. The mean acromiocoracoid distance and acromioglenoid distance were 3.09 and 2.47 cm, respectively. The most common shape of the acromion process noted was quadrangular in 40% of scapulae. In 90% of scapulae, the anterior 2/3 rd of inferior surface was rough and in 80% scapulae, enthesophytes were present. Conclusions: This study will help the clinicians in understanding and curing various shoulder joint disorders.